Asthmatic subjects with allergy have elevated levels of IgE+ B cells in the airways - Oliveria, John-Paul; Salter, Brittany M.; Phan, Stephanie; Obminski, Caitlin D.; Munoz, Caroline E.; Smith, Steven G.; Scime, Tara; Watson, Rick M.; Sehmi, Roma; Gauvreau, Gail M. (Journal of allergy and clinical immunology, 2017)
To The Editor: Allergic asthma is an IgE-mediated disease whereby inhaled allergens cross-link membrane-bound IgE on the surfaces of mast cells and basophils, inducing the activation and release of proinflammatory mediators, and driving type-2 inflammation and the manifestation of clinical symptoms.1 Because B cells solely produce IgE, it is evident that these cells play a crucial role in initiating allergen-induced inflammatory processes. The frequency and absolute numbers of IgG+ B cells, evaluated as a control cell population, showed a higher tendency, but no statistical difference in asthmatic subjects compared with the nonasthmatic subjects when measured in the sputum or blood (P > .05) (see Fig E6 in this article's Online Repository at www.jacionline.org). Variable Controls (n = 10) Asthmatic subjects with allergy (n = 18) Subjects with allergy (n = 19) Sex (M/F), no. 4/6 8/10 10/9 Age (y) 37.1 ± 3.8 31.8 ± 3.3 26.2 ± 2.4 FEV1, % of predicted 94.9 ± 2.6 91.6 ± 1.6 98.2 ± 2.8 Methacholine PC20 (mg/mL), geometric mean (95% CI) >16 3.7 (2.2, 6.4)∗† >16 Sputum eosinophils (%) 0.08 ± 0.04 1.8 ± 0.3∗† 0.6 ± 0.1 Sputum total IgE (IU/mL) 0.5 ± 0.0 3.7 ± 1.3∗ 0.8 ± 0.2 Sputum BAFF (pg/mL) 32.8 ± 12.3 230.3 ± 53.4∗† 24.0 ± 7.0 Blood eosinophils (%) 1.8 ± 0.4 4.8 ± 0.5∗ 3.2 ± 0.4 Plasma total IgE (IU/mL) 19.8 ± 3.4 288.7 ± 34.3∗† 107.6 ± 29.9 Skin test positive to Cat dander 0 15 12 Horse dander 0 12 5 House...